Voices returning. Memory and inheritance in three contemporary Brazilian novels (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article attempts to address a number of fictional texts of brazilian youth authors - Tatiana Salem Levy, Michel Laud and Paloma Vidal- that working around the issue of migra- tion from characters seeking to rediscover his past outsi- de Brazil. Thus, after what could be considered a first and “successful” process of nationalization in the early decades of the twentieth century, these “children and grandchildren of migrants back to examine those movements, with the aim of investigating the veracity of these accounts, the texture of the unsaid, and performativity that both -stories and silen- ces- seem to keep producing despite the time elapsed.
Keywords: Migration; Memory; Literature